Diabetogenic action of pituitary hormones on adrenalectomized hypophysectomized dogs - Houssay, Bernardo Alberto (1956)
THE diabetogenic action of the anterior pituitary extracts was demonstrated in hypophysectomized-pancreatectomized toads by Houssay and Biasotti (1). This action was not obtained in pancreatectomized cats and rats in the absence of adrenals (2, 3). But the diabetogenic action of the anterior pituitary extract was obtained in other adrenalectomized animals : a) toads deprived of adrenals and pancreas (4); b) toads deprived of hypophysis, pancreas, kidney and adrenals (5): c) toads deprived of hypophysis, pancreas and adrenals (4, 6); in cases 6 and c, the diabetogenic action was diminished by the absence of the adrenals. The diabetogenic action of the pituitary was also observed in mammals deprived of the adrenals such as: d) dogs with reduction of the pancreatic mass, deprived of both adrenals and maintained with cortico-adrenal extract (7, 8) or with desoxycorticosterone (8); e) dogs with reduction of the pancreatic mass, deprived of the adrenals, maintained only with sodium chloride and not receiving adrenal hormones (8); some of these dogs were also deprived of the thyroid. All these experiments demonstrated that hypophyseal diabetes may be obtained without the presence or participation of the adrenals.